Efficiency of Herbal Galactogogues in Galactopoiesis- A Literature Review (International Journal of Food and Nutritional Sciences, 2025)
Breast-feeding is essential for both new-born and nursing mothers. Breast milk provides optimal nutrition as well as immunity to new-born and lifelong health benefits to both mothers and children. But conditions like insufficient milk production or agalactia due to various barriers may cause inadequate nourishment of their babies, weight-loss for neonates, prompting for supplementation with formula feeding. Multiple plants are used as galactogogues worldwide during lactation period. Herbal galactogogues are naturally-derived plant products or herbs that help to augment, maintain and stimulate milk production in lactating mothers e.g cumin, fenugreek, shatavari, moringa, garlic, anise, sesame seeds, fennel seeds, milk thistle ,amaranth etc. The mechanisms of action of herbal galactogogues are different from each other. Some herbs like cumin, moringa, garlic act by stimulating prolactin hormone secretion, increasing mammary gland development and thus enhancing milk ejection reflex. Some of herbs like fenugreek and shatavari exhibit their lactogenic effects by influencing hormonal pathways. Despite of widespread use of traditional herbs there is limited and inconsistent scientific research and evidence on safety, usage, doses and efficacy of these herbs. Some clinical trials show positive impacts e.g increased milk production, weight gain in neonates while others show no significant improvement compared to placebo. By combining traditional knowledge and scientific research and approaches, the therapeutic uses of herbal galactogogues can be increased, thus supporting better and successful lactation results.